(untitled) (Comillas Journal of International Relations, 2024)
Unpacking the experience of Ecojesuit as a global network helps in exploring new ways of collaborating across institutions and committed individuals for better participation in global processes. Ecojesuit, a tiny voice at the fringes of the United Nations (UN) meetings on climate and sustainability, adds effort to the broader social commitment for global action. It connects with other organizations sharing goodwill, capacities and voices caring for our common home and those struggling in the local context of climate disasters. While COP28 has been a great disappointment for those seeking fossil fuel phaseout, research of the International Panel on Climate Change (IPCC) is increasingly upheld. Such participation in international relations deepens the Jesuit Universal Apostolic Preferences (UAPs) and Jesuit regional Conferences in apostolic planning. The process of growing a Jesuit network of broad collaboration takes decades; each revision involves greater participation and inclusion of present realities and meaning in life.